The mechanisms of gallium-catalysed skeletal rearrangement of1,6-enyneseInsights from quantum mechanical computations - Borketey, Joseph Bortey; Opoku, Ernest; Tia, Richard; Adei, Evans (Elsevier Inc, 2020)
An article published by Elsevier Inc. and also available at https://doi.org/10.1016/j.jmgm.2019.107476